2020
DOI: 10.1128/msphere.00801-19
|View full text |Cite
|
Sign up to set email alerts
|

Origin of OXA-23 Variant OXA-239 from a Recently Emerged Lineage of Acinetobacter baumannii International Clone V

Abstract: Over the last few decades, carbapenemase-producing Acinetobacter baumannii has become a major cause of nosocomial infections all over the world. However, the genome identity of lineages of this species in Latin America has not been studied as much as in developed countries. Here, through a population genomics approach considering the whole genomes of 148 isolates (almost 40 from Mexico and Honduras), we describe the recent emergence of the lineage sequence type 758 (ST758), which belongs to the international c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 40 publications
1
45
1
Order By: Relevance
“…The data reported here confirms that at least four different CCs are circulating in the different hospitals from a single metropolitan area from Northeastern Brazil, with no obvious association found between any of the CCs/STs and variables such as hospitals, collection years or sampling methods. This is in contrast with other studies which usually reports outbreaks of either a single ST or closely related ones (Mosqueda et al, 2013;Wright et al, 2014;Li et al, 2015;Ou et al, 2015), although a recent report from Latin America has also found multiple lineages of MDR A. baumannii coexisting within the same hospital (Graña-Miraglia et al, 2020). Among those CCs founds here, CC1, CC15, and CC113 (ST25) are considered globally spread Acinetobacter clonal complexes, having been isolated from different parts of the world for more than 20 years (Diancourt et al, 2010;Di Nocera et al, 2011;Di Popolo et al, 2011;Karah et al, 2012;Sahl et al, 2015;Gaiarsa et al, 2019).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The data reported here confirms that at least four different CCs are circulating in the different hospitals from a single metropolitan area from Northeastern Brazil, with no obvious association found between any of the CCs/STs and variables such as hospitals, collection years or sampling methods. This is in contrast with other studies which usually reports outbreaks of either a single ST or closely related ones (Mosqueda et al, 2013;Wright et al, 2014;Li et al, 2015;Ou et al, 2015), although a recent report from Latin America has also found multiple lineages of MDR A. baumannii coexisting within the same hospital (Graña-Miraglia et al, 2020). Among those CCs founds here, CC1, CC15, and CC113 (ST25) are considered globally spread Acinetobacter clonal complexes, having been isolated from different parts of the world for more than 20 years (Diancourt et al, 2010;Di Nocera et al, 2011;Di Popolo et al, 2011;Karah et al, 2012;Sahl et al, 2015;Gaiarsa et al, 2019).…”
Section: Discussioncontrasting
confidence: 98%
“…Among those CCs founds here, CC1, CC15, and CC113 (ST25) are considered globally spread Acinetobacter clonal complexes, having been isolated from different parts of the world for more than 20 years (Diancourt et al, 2010;Di Nocera et al, 2011;Di Popolo et al, 2011;Karah et al, 2012;Sahl et al, 2015;Gaiarsa et al, 2019). In contrast, CC79 strains have been described mostly from North and South America but also in Europe (Karah et al, 2012;Villalón et al, 2013;Chagas et al, 2014;Wright et al, 2014;Bado et al, 2018;Da Silva et al, 2018;Levy-Blitchtein et al, 2018;Graña-Miraglia et al, 2020), while ST113 (also belonging to CC113) was described originally in the Middle East but has more recently mostly been reported from South America (Bonnin et al, 2013;Clímaco et al, 2013;Girlich et al, 2014). Here, the availability of draft genome sequences from multiple strains from various STs and clonal complexes co-existing in the same environments allowed a large-scale comparison of the multiple elements associated with their antibiotic resistance and virulence.…”
Section: Discussionmentioning
confidence: 90%
“…This lineage emerged rather recently (about 22 years ago) and since then it has spread in many countries in Latin and North America; notably, strains from this lineage are not only carbapenem resistant but also multidrug resistant. In terms of acquired oxacillinases (OXAs), this lineage presents the worldwide-distributed OXA-23-like family but also the less disseminated OXA-40-like family [24].…”
Section: Plos Onementioning
confidence: 99%
“…Isolates belonging to IC5 are members of CC PAS and are found at particularly high frequency in Latin America (15,57,67,68). The allele profiles of the founder sequence types of CC PAS 158 and CC PAS 79 (ST PAS 158 and ST PAS 79 respectively) are quite different, sharing only 1 of the 7 alleles (rplB allele 4), which at the nucleotide level translates to 13 SNPs.…”
Section: Discussionmentioning
confidence: 99%